Faktor-Faktor Lingkungan Fisik Rumah Yang Berhubungan Dengan Kejadian Pneumonia Pada Balita Di Wilayah Kerja Puskesmas Pangandaran Kabupaten Ciamis - Yulianti, Lina; Setiani, Onny; Darundiati, Yusniar Hanani (Jurnal Kesehatan Lingkungan Indonesia, 2012)
Background : Based on the Profile of Ciamis District Health Department in 2010, pneumococcal disease is asequence of infectious disease in children is quite hight, still in the top ten of outpatient clinicmost diseases,whereas in the working area of Pangandaran health center in 2011 there were 61 cases of pneumococcal disease(1.56%). The case is suspected to the condition of the physical environment of the house where children live.Therefore, the research was done in order to analyze factors of house physical environment on pneumoniaoccurrence in children under 5 years.Methods : This study was an observational research with a case control design. The research subjects consistedof case groups and control groups, with each sample of 46 people. Research variables consisted of wall type, floortype, ventilation condition of the house, ventilation condition of the bedrooms, house occupancy density, theseparation of a toddler’s bedroom, bedroom occupancy density, the location of the kitchen, the lighting conditionsin the house, temperature, humidity kind of, cooking fuel, the dangers rank of smoking, the practice of using ofmosquito coils. Data were collected through interviews and observation. The research data were analyzed byunivariate, bivariate and multivariate logistic regression.Result : Bivariate analysis results obtained information that there were three variables that have an associationwith the occurrence of pneumonia in toddlers, but according to a multivariate analysis known that there was adominant variable that was lighting conditions in the house with Odds Rasio 21,875; 95% CI 4,353 to109,933.Conclusion : . This study concluded that the physical condition of the house still needs improvements, especiallyto achieve that required condition needs, ventilation improvement both in house and in the bedroom.Key words : Pneumonia, toddler, house’s physical environment, Ciamis.